Scientific and Philosophical Heritage of Abulkasim Qushayri - Hoshimovich, Kodirov Davronbek (International Journal on Integrated Education, 2023)
The article analyzes the scientific and philosophical heritage of the thinker Abulkasim Kushayri, who systematized the terms of the Sufi teaching. Also, the article reveals the classification of sources in the study of Qushayri's life, the period in which he lived, and his scientific and philosophical heritage.